Penanaman Nilai-Nilai Kewirausahaan Pada Divisi Ekonomi Kreatif DEMA STAI Al-Hamidiyah Jakarta - Karmila Rianda; Hartin Kurniawati; Anjelita Nur Isiami; Nurhasanah Nurhasanah (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research has objectives including: (1) knowing the implementation of instilling entrepreneurial values in the creative economy division, (2) discussing inhibiting factors and supporting factors for the cultivation of entrepreneurial values in the creative economy division, (3) solutions in overcoming inhibiting factors. The research approach used is a qualitative approach with data collection through interviews, observation, documentation. Data analysis uses three stages, namely data reduction, data presentation, conclusions. The results of the study explained that: (1) the creative economy division was given the cultivation of entrepreneurial values; the value of cooperation; responsibility; creativity with the pre-order system activities at STAI Al-Hamidiyah Jakarta, (2) inhibiting factors in instilling entrepreneurial values; communication and cooperation between members of the creative economy division are poorly established; The means of entrepreneurship at STAI Al-Hamidiyah Jakarta are inadequate, then supporting factors include; DEMA supervisors and lecturers support the pre-order system in the creative economy division; BPH contributes to the implementation of the pre-order system in the creative economy division, (3) The solution in overcoming inhibiting factors is to consistently hold meetings to evaluate pre-order and creative activities in promoting the products of the Creative Economy Division to be visible to the campus and provided support through means in entrepreneurship. The conclusion is that the entrepreneurial values in the creative economy division that have been instilled consist of three values, namely the value of cooperation between division members in managing products, the value of responsibility in the duties of their respective members, and the value of creativity in managing selling products. Keywords: Entrepreneurial Values, Creative Economy